A Study of Consumer Responses to Multimedia Product Information via QR Codes - ดนัยดุษฎีกุล เจษฎาพร; เทียนงาม ลัดดา; ปานสุวรรณ ดุสิตา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purpose of this study was to: 1) develop multimedia product information for power bank products linked via QR code, 2) assess the quality of multimedia product information by experts, and 3) examine consumer responses to multimedia product information via QR code. The sample consisted of 5 experts and 50 consumers, selected through purposive sampling. The research instruments included multimedia product information developed in the form of text, images, and videos linked through a QR code, an expert media quality evaluation form, and a consumer feedback questionnaire. Consumers scanned the QR code to access product information and then responded to the questionnaire. Data were analyzed using means and standard deviations. The findings revealed that the overall quality evaluation of the multimedia product information via QR code by experts was at a high level (x̄= 3.91, S.D. = 0.62). Additionally, consumer feedback on multimedia product information via QR code was also at a high level (x̄= 4.08, S.D. = 0.81). These results demonstrate that the developed multimedia product information via QR code is appropriate for use as a tool for communicating power bank product information and effectively facilitates consumer access to product details, enhancing ease of understanding and supporting informed purchase decisions.